Hubungan Pengetahuan Remaja Tentang Kesehatan Reproduksi Dengan Tingkat Kecemasan Pada Remaja Di Desa Pandean Kabupaten Sukoharjo Tahun 2017 - Amarseto, Binuko; Ariyanti, Lilik (Jurnal Farmasi (Journal of Pharmacy), 2018)
Reproductive health is a complete physical, mental and social welfare and not only the absence of a disease or weakness, in all matters relating to the reproductive system and its functions and processes. Knowledge about reproductive health is of course very important in relation to the development of the psychological life of adolescents who in this case often begin to deal with matters related to reproductive problems, in this case of course the matter of sexuality and orientation which will later result in self-confidence and anxiety self. This study aims to determine the relationship of adolescent knowledge about reproductive health to the level of anxiety in adolescents in the village of Pandean, Sukoharjo District 2017. This research is explanatory research with cross sectional design. Data collection is done by using questionnaires. The research sample was teenagers totaling 45 people from a population of 81 people using simple random sampling technique. Data analysis using Pearson Product Moment test with a significance level of 5%. The dependent variable in this study is adolescent anxiety, while the independent variable in this study is adolescent knowledge about reproductive health. The results of this study obtained a sample of 45 adolescents in Pandean village, with the highest number of sexes being men with 30 respondents (66.7%), the majority of respondents still attending school and taking high school education (69%). For the results of the research data description, the average value of knowledge is 15.16 while the average value of anxiety is 105.69. The results of the test data using Pearson Product Moment get the results of p = 0.007 (p <0.05) which means the relationship of adolescent knowledge about reproductive health with the level of anxiety in adolescents in Pandean Village, Sukoharjo Regency, with a coefficient of 0.396 which means the relationship of adolescent knowledge about reproductive health with anxiety has a low relationship strength.